2014
DOI: 10.1016/j.meatsci.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for meat quality traits of Australian lamb meat

Abstract: Genetic parameters were estimated for a range of meat quality traits recorded on Australian lamb meat. Data were collected from Merino and crossbred progeny of Merino, terminal and maternal meat breed sires of the Information Nucleus programme. Lambs born between 2007 and 2010 (n=8968) were slaughtered, these being the progeny of 372 sires and 5309 dams. Meat quality traits were found generally to be of moderate heritability (estimates between 0.15 and 0.30 for measures of meat tenderness, meat colour, polyuns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
62
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 40 publications
13
62
1
8
Order By: Relevance
“…Of all muscle traits measured, pH 24 had the greatest magnitude of effect on chroma, which is an important component in the evaluation of meat colour by consumers (AMSA, 2012). The impact of pH 24 of meat redness, yellowness, hue and chroma again appears to be independent of other muscle variables including myoglobin, a reasonable finding given the low phenotypic correlation (-0.01) reported between lamb loin pH 24 and myoglobin concentration (Mortimer et al, 2014).…”
Section: Accepted M Manuscriptmentioning
confidence: 55%
See 1 more Smart Citation
“…Of all muscle traits measured, pH 24 had the greatest magnitude of effect on chroma, which is an important component in the evaluation of meat colour by consumers (AMSA, 2012). The impact of pH 24 of meat redness, yellowness, hue and chroma again appears to be independent of other muscle variables including myoglobin, a reasonable finding given the low phenotypic correlation (-0.01) reported between lamb loin pH 24 and myoglobin concentration (Mortimer et al, 2014).…”
Section: Accepted M Manuscriptmentioning
confidence: 55%
“…Increasing iron reduced meat lightness to a slightly lesser magnitude than myoglobin, though to a greater extent than pH 24 . The consistent direction and similar magnitude of impact of iron and myoglobin on loin lightness is unsurprising given the high reported correlations between iron and myoglobin (Mortimer et al, 2014) and their close biochemical association; iron being an essential component of the myoglobin pigment. However, iron is a less sensitive measure of myoglobin pigmentation given that total iron measures capture heme iron within other muscle proteins such as ferritin, as well as non-heme iron, hence the reduced magnitude of impact of iron compared to myoglobin.…”
Section: Accepted M Manuscriptmentioning
confidence: 90%
“…Falling back on earlier studies conducted by Moltimer et al (18), pH measurement is one of the most common criteria of meat quality assessment, as it informs about the rate of post-slaughter glycolysis, which is an efficient prognosticating tool. The pH measurement results point to the correct course of postslaughter transformations in the assessed beef muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Work by showed that selection for improved LMY% using increased sire PEMD and reduced sire PFAT had a negative impact on the eating quality of longissimus and semimembranosus samples, partially through their impact on intramuscular fat percentage. Therefore future multi-trait indexes are required that balance eating quality (reflected through intramuscular percentage) with the existing growth and carcass traits (Mortimer et al, 2014;Swan, Pleasants, & Pethick, 2015). More widespread…”
Section: Accepted M Manuscriptmentioning
confidence: 99%